1991
DOI: 10.1007/bf00312767
|View full text |Cite
|
Sign up to set email alerts
|

Sterile UGA nonsense mutants of fission yeast

Abstract: Eight sterile mutants, which regain their fertility upon reactivation of an inactivated UGA suppressor allele of the serine tRNA gene sup3, are shown to carry UGA nonsense alleles of two established ste genes, ste1 (one mutant) and ste6 (two mutants), and of two novel genes, ste9 (four mutants) and ste10 (one leaky mutant of ras1-/ste5-like cell morphology). The mutant alleles of ste1 and ste9 lead to a defect in both conjugation and meiosis, whereas those of ste6 and ste10 affect mating only. Two of the four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Instead, mating is most efficiently triggered by nitrogen starvation, and immediately followed by meiosis and sporulation [14], [15]. From classical genetic screens, about 20 mating genes have been identified in S. pombe , which are called ste (for sterile) or ral (for ras -like) genes [16 and references therein]. According to PomBase [17], 15 ste and ral genes have been cloned thus far.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, mating is most efficiently triggered by nitrogen starvation, and immediately followed by meiosis and sporulation [14], [15]. From classical genetic screens, about 20 mating genes have been identified in S. pombe , which are called ste (for sterile) or ral (for ras -like) genes [16 and references therein]. According to PomBase [17], 15 ste and ral genes have been cloned thus far.…”
Section: Resultsmentioning
confidence: 99%
“…Many sporulation‐deficient mutants and sterility mutants have been isolated and characterized in Sz. pombe (Bresch et al ., 1968; Leupold and Sipiczki, 1991; Thuriauz et al ., 1980), and most of these have exhibited defects in the regulation of the distinct steps of sporulation or meiosis. However, there have been no investigations on the relationship between sexual conjugation and cell surface glycosylation in Sz.…”
Section: Resultsmentioning
confidence: 99%
“…As described below in detail, the ste9 mutant conformed to this criterion and exhibited defects indistinguishable from those of the rum1 mutant. The ste9 mutant was identified previously (Leupold and Sipiczki, 1991), but its molecular characterization has not been attempted. To determine its coding product, the ste9 ϩ gene was isolated by rescuing the sterility of its mutant.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the DNA content of the cells at 30°C revealed that the apparent 1C peak corresponding to the G 1 population was seen in the cdc10 ts strain, but no such population was found in the ste9 cdc10 ts strain ( Figure 4B). The DNA profiles of both strains at 32°C were also quite different, in that appearance of the Leupold and Sipiczki (1991). ste9-59 is a novel allele encoding partially active protein (our unpublished result, see text).…”
Section: Ste9 and Wee1 Mutations Cause Synthetic Lethalitymentioning
confidence: 85%